Development and initial testing of a Personalized Environmental Control System (PECS) - Kazanci, Ongun B.; Shinoda, Jun; Yin, Hang; Bogatu, Dragos-Ioan; Watanabe, Futa; Kaneko, Yosuke; Olesen, Bjarne W. (CLIMA 2022 conference, 2022)
Personalized Environmental Control Systems (PECS) condition the immediate surrounding of occupants in contrast to conventional HVAC systems. PECS have several advantages including allowing occupants to adjust their immediate surroundings according to their preferences, which could improve their satisfaction with the indoor environment, which may lead to higher productivity. PECS can also lead to noticeable energy savings, if implemented effectively in buildings. The present study explains the development process and initial testing of a novel PECS. The PECS had heating, cooling, and ventilation functions, together with the possibility of adjusting lighting color and brightness. Ventilation and cooling were provided from a desktop air terminal device, and heating was provided by a curved panel covering the lower body from the thigh to the lower leg of a seated occupant. A thermal manikin was used to quantify the heating and cooling performance of the different versions of the PECS. The most recent prototype was able to provide a cooling effect up to 6 K (calculated by the manikin-based equivalent temperature difference) to the left side of the face, and a heating effect of up to 5 K to the left and right thighs. The cooling and heating effect of the whole body was up to 0.3 K and 1.3 K, respectively. A Peltier element was introduced to lower the supply air temperature from the PECS, but had limited effect on the cooling effect despite the large increase in power use. When implementing a Peltier element in PECS, the generated waste heat must be handled so that it does not interfere with the cooling.